2020
DOI: 10.1111/febs.15290
|View full text |Cite
|
Sign up to set email alerts
|

Flavodoxin hydroquinone provides electrons for the ATP‐dependent reactivation of protein‐bound corrinoid cofactors

Abstract: Corrinoid-dependent enzyme systems rely on the super-reduced state of the protein-bound corrinoid cofactor to be functional, for example, in methyl transfer reactions. Due to the low redox potential of the [Co II ]/[Co I ] couple, autoxidation of the corrinoid cofactor occurs and leads to the formation of the inactive [Co II ]-state. For the reactivation, which is an energydemanding process, electrons have to be transferred from a physiological donor to the corrinoid cofactor by the help of a reductive activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Since corrinoids are highly reactive in their superreduced active state, they undergo spontaneous autooxidation leading to an inactivation of the CoP. To return the corrinoid cofactor to the active state, so-called activating enzymes use ferredoxin/ flavodoxin to reductively activate the corrinoid protein (Dürichen et al, 2019;Kißling et al, 2020). MTI confers the substrate specificity and a BLAST search using the Eubacterium limosum MTI (MttB, WP_038351887.1; (Kountz et al, 2020)) as query showed that the genome of E. callanderi KIST612 encodes 32 different MTI enzymes (Table S1), underlining the importance of methyl groups as carbon and energy source for E. callanderi KIST612.…”
Section: Resultsmentioning
confidence: 99%
“…Since corrinoids are highly reactive in their superreduced active state, they undergo spontaneous autooxidation leading to an inactivation of the CoP. To return the corrinoid cofactor to the active state, so-called activating enzymes use ferredoxin/ flavodoxin to reductively activate the corrinoid protein (Dürichen et al, 2019;Kißling et al, 2020). MTI confers the substrate specificity and a BLAST search using the Eubacterium limosum MTI (MttB, WP_038351887.1; (Kountz et al, 2020)) as query showed that the genome of E. callanderi KIST612 encodes 32 different MTI enzymes (Table S1), underlining the importance of methyl groups as carbon and energy source for E. callanderi KIST612.…”
Section: Resultsmentioning
confidence: 99%
“…The unique methyl ether cleavage is achieved by the action of supernucleophilic Co(I) reactive species generated in the Co-corrinoid O-methyltrans- ferase enzyme. 24 Since three A. dahurica furanocoumarins, compounds 1, 2, and 6 in Figure 1, contain methyl aryl ether functional group, each furanocoumarin was reacted to Blautia sp. MRG-PMF1 strain to examine whether the strain is responsible for the conversion.…”
Section: Resultsmentioning
confidence: 99%
“…MRG-PMF1 strain was reported to metabolize polymethoxyflavones to the corresponding flavones by the cleavage of methyl aryl ether groups. The unique methyl ether cleavage is achieved by the action of supernucleophilic Co­(I) reactive species generated in the Co-corrinoid O -methyltransferase enzyme . Since three A.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Encouraged by reductive dehalogenation in the presence of added riboflavin, we tested more flavin mononucleotide (FMN)-binding flavodoxins (Flds) for suitability as electron shuttlers. We expressed and purified five flavodoxins from E. coli (EcFld), 43 Azobacter vinelandii (AvFld), 44,45 Chlorobium phaeovibroides (CpFld), 46 Acetobacterium dehalogenans (AdFld), 47 , and D. hafniense DCB-2 (DhFld). 47 Purified Flds were largely apo and were supplemented with FMN in biochemical assays.…”
Section: T H Imentioning
confidence: 99%
“…We expressed and purified five flavodoxins from E. coli (EcFld), 43 Azobacter vinelandii (AvFld), 44,45 Chlorobium phaeovibroides (CpFld), 46 Acetobacterium dehalogenans (AdFld), 47 , and D. hafniense DCB-2 (DhFld). 47 Purified Flds were largely apo and were supplemented with FMN in biochemical assays. Formation of phenol was observed after incubating 50 μM DhFld with lysates containing DaPFOR and RdhC1 in the presence of necessary cofactors.…”
Section: T H Imentioning
confidence: 99%